Enhancement of Mathematics Learning Outcomes in First-Grade Students at SD Inpres Palsatu Kupang Through the Use of 3D Media - Maria Gaudensiana Sona (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2025)
This research aims to improve mathematics learning practices in first-grade students at SD Inpres Palsatu Kupang through the use of three-dimensional media, specifically smart ladders. The study was conducted in two cycles using Classroom Action Research methodology, which includes planning, implementation, observation, and reflection. In the first cycle, observations indicated that several aspects of learning were not optimal, with teacher and student activity percentages below the ideal target. Consequently, improvements were made in the second cycle. Results in the second cycle showed significant improvements in classroom management, use of learning media, and student engagement, with teacher and student activity percentages reaching 75% on almost all indicators. This research demonstrates that effective use of three-dimensional media and continuous improvement in lesson planning and implementation can significantly enhance students' mathematics learning outcomes.